The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2010
DOI: 10.1111/j.1540-8159.2010.02725.x
|View full text |Cite
|
Sign up to set email alerts
|

Diurnal Heart Rate Patterns in Inappropriate Sinus Tachycardia

Abstract: Patients with IAST and elevated average daily HR exhibit normal diurnal variation around a higher mean HR. In contrast, patients with IAST and lower average daily HR had an exaggerated morning rise in HR. These diurnal patterns may be useful to classify the pathophysiology of IAST.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
15
0
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 12 publications
(16 citation statements)
references
References 27 publications
0
15
0
1
Order By: Relevance
“…Continuous ambulatory HR monitoring has previously shown that HR undergoes diurnal variation [17,24]. HR was maximal in the morning (10 am) with a subsequent progressive decline throughout the day until a nadir in the early morning hours just prior to waking, after which HR begins to rise again [17]. This variability might be an adaptive advantage to allow the human to rise in the morning to meet the challenges of a new day.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Continuous ambulatory HR monitoring has previously shown that HR undergoes diurnal variation [17,24]. HR was maximal in the morning (10 am) with a subsequent progressive decline throughout the day until a nadir in the early morning hours just prior to waking, after which HR begins to rise again [17]. This variability might be an adaptive advantage to allow the human to rise in the morning to meet the challenges of a new day.…”
Section: Discussionmentioning
confidence: 99%
“…Blood pressure and heart rate exhibit considerable variation over a 24-hour period[35,9,17,24] as a result of diurnal variations in emotional and behavioral states[18,22], baroreflex sensitivity[5,13], renin-angiotensin system activity[23], plasma catecholamine levels[4,23], and adrenergic tone[11]. The measurement of blood pressure and heart rate in the supine and standing positions forms the basis of orthostatic testing, which is crucial to the evaluation of a number of neurocardiogenic disorders including syncope, autonomic failure, and POTS [12,26].…”
Section: Introductionmentioning
confidence: 99%
“…IST is a diagnosis of exclusion, requiring that other causes of sinus tachycardia be investigated. IST is often difficult to identify and treat, particularly given the multiple underlying pathophysiologic processes . IST seems to be more prevalent in women, and in particular, women who are employed within healthcare .…”
Section: Introductionmentioning
confidence: 99%
“…An alternative explanation for the time‐related HR reduction in POTS with placebo is a background cardiovascular variability unrelated to therapy. Blood pressure (BP) and HR are known to exhibit significant diurnal variability over a 24 h period, with an increase in these measures in the early morning that is associated with sympathetic activation . Furthermore, numerous cardiovascular events, such as myocardial ischaemia, stroke and arrhythmia, exhibit some degree of circadian variability, with a peak in event rates in the early morning …”
Section: Introductionmentioning
confidence: 99%
“…Blood pressure (BP) and HR are known to exhibit significant diurnal variability over a 24 h period, with an increase in these measures in the early morning that is associated with sympathetic activation. [13][14][15] Furthermore, numerous cardiovascular events, such as myocardial ischaemia, stroke and arrhythmia, exhibit some degree of circadian variability, with a peak in event rates in the early morning. [16][17][18] To determine which of these possibilities may best explain the decrease in standing HR with placebo over time, we performed a prospective randomized cross-over trial comparing an open-label no treatment (NoRx) intervention with a blinded placebo in POTS patients.…”
Section: Introductionmentioning
confidence: 99%